Bisão, Arquiteto da Paisagem: repertório gráfico e estratégia formal - Lima, Emiliano Cavalcante Teixeira (2024)
This research took as its starting point the collection of Otacílio Teixeira Lima Neto, known as Bisão (1946-2013), investigating his work as a landscape architect largely during his activity as a public servant of the Fortaleza Municipal Administration – PMF. The focus is on his early years of production, specifically: the Beira-Mar Boardwalk and the Theatro José de Alencar, both in Fortaleza (Ceará), and the Anauá Park in Rio Branco (Roraima). The work aims to investigate the architect's work in search of patterns related to the use of form to solve problems. A tool, regulations and criteria were developed to assist in the investigation and verification of the results obtained. For this purpose, it made use of contents advocated by authors who produced studies on form, thus obtaining the necessary theoretical basis to confirm their formal strategies. Finally, it was identified, both in the pre-established scope and in some other works brought to reinforce the analysis, that there was indeed a geometric and conceptual spectrum of wide use by the architect.